Surface crystallization and magnetic properties of Fe84.3Cu0.7Si4B8P3 soft magnetic ribbons. (1st September 2015) - Lopatina, E.; Soldatov, I.; Budinsky, V.; Marsilius, M.; Schultz, L.; Herzer, G.; Schäfer, R.
Abstract: The magnetic microstructure and hysteresis properties of Fe84.3 Cu0.7 Si4 B8 P3 soft magnetic ribbons have been investigated by Kerr-microscopy, Kerr-magnetometry and inductive hysteresis measurements. Crystalline surface layers were already present after quenching, causing an out-of-plane anisotropy in the amorphous bulk. Annealing at elevated temperature leads to nanocrystallization in the inner part of the ribbon and to a gradual decline of the perpendicular anisotropy with increasing temperature. The surface magnetization process is determined by the coercive motion of 180° domain walls along the ribbon axis, while the bulk magnetization process is dominated by reversible rotation of magnetization.